Perilaku Pencarian Informasi Covid 19 dan Implikasinya pada Strategi Komunikasi - Puji Rianto; Subhan Afifi; Puji Hariyanti (Komunika: Jurnal Ilmu Komunikasi, 2023)
The Covid 19 pandemic that entered Indonesia since the end of 2019 or early 2020 has decreased significantly from the number of sufferers. In this regard, the crisis provides many lessons for the community and policy makers. One of the important lessons is how people seek information and how government communication policies are formulated. This research was conducted to examine the behavior of people seeking information during the Covid 19 Pandemic, and how this has implications for communication policies. The research was conducted using mixed methods. Quantitative research is conducted through online surveys and big data analysis, while qualitative research is conducted through focus group discussions. The results showed that the media used by the public to obtain information was very diverse. Social media is the most widely used. But unfortunately, the level of trust in information from social media is very low. Television is the most trusted medium. Communication strategies should be based on people's behavior in seeking information so that crisis communication regarding Covid 19 can be carried out properly